Detection of Root Physiological Parameters and Potassium and Calcium Currents in the Rhizoplane of the Apple Rootstock Superior Line 12-2 With Improved Apple Replant Disease Resistance - Mao, Yunfei; Yin, Yijun; Cui, Xueli; Wang, Haiyan; Su, Xiafei; Qin, Xin; Liu, Yangbo; Hu, Yanli; Shen, Xiang (Frontiers in Plant Science, 2021)
The cultivation of resistant rootstocks is one of the more effective ways to mitigate apple replant disease (ARD). We performed an ion current test, a pot experiment, and a pathogen infection test on the apple rootstocks 12-2 (self-named), T337, and M26. The ion current test showed that exposure to ARD soil extract for 30 min had a significant effect on K+ ion currents at the meristem, elongation, and mature zones of the M26 rhizoplane and on Ca2+ currents in the meristem and elongation zones. ARD also had a significant effect on Ca2+ currents in the meristem, elongation, and mature zones of the T337 rhizoplane. Exposure to ARD soil extract for 5 min had a significant effect on K+ currents in the meristem, elongation, and mature zones of 12-2 and on the Ca2+ currents in the elongation and mature zones. Compared to a 5-min exposure, a 30-min exposure to ARD extract had a less pronounced effect on K+ and Ca2+ currents in the 12-2 rhizoplane. The pot experiment showed that ARD soil had no significant effect on any root architectural or physiological parameters of 12-2. By contrast, ARD soil significantly reduced some root growth indices and the dry and fresh weights of T337 and M26 compared with controls on sterilized soil. ARD also had a significant effect on root metabolic activity, root antioxidant enzyme activity (except superoxide dismutase for T337), and malondialdehyde content of T337 and M26. Pathogen infection tests showed that Fusarium proliferatum MR5 significantly affected the root structure and reduced the root metabolic activity of T337 and M26. It also reduced their root antioxidant enzyme activities (except catalase for T337) and significantly increased the root malondialdehyde content, reactive oxygen levels, and proline and soluble sugar contents. By contrast, MR5 had no such effects on 12-2. Based on these results, 12-2 has the potential to serve as an important ARD-resistant rootstock.